L2 Motivation in Process Drama: The Cycle of L2 Motivation - Ma, Ling (Trinity College (Dublin, Ireland). School of Education, 2021)
Motivation is widely considered as a significant variable in the process of Second Language Acquisition (SLA). It is an important factor that contributes to the competence of a second language for adults (Marinova-Todd et al., 2000). This research examines the connection between process drama and motivation in Second Language teaching and learning. It is a desk-based research study, based on qualitative secondary research (Largan & Morris, 2019). Specifically, sixteen studies were identified to investigate Second Language (L2) motivation in process drama. The research explores the potent connection between L2 motivation being portrayed in the process drama tradition and emotional factors. These were classified under four main themes: first, a student-centered and collaborative bonding between students and the teacher in drama; second, a conducive learning environment where students are free to make mistakes; third, entering a ‘flow’ experience, which can be generated when students are challenged appropriately; and lastly, the autonomy that results from the learning content being designed by students. These four key themes are inter-connected and incremental and were conceptualized in the analysis as a cycle, namely the Cycle of L2 Motivation in process drama. Three parameters emerged from the analysis as essential to fuel this cycle: dramatic tension, support, and authenticity. With the findings abovementioned, L2 motivation in process drama is portrayed as a dynamic cycle of interconnected factors. The research argues that L2 motivation origins from the urge to bridge the gap between the demand of L2 proficiency in drama, and one’s current L2 proficiency. The research finally points to some recommendations for potential directions of the application of process drama in L2 teaching.
Keywords: Drama in Education; Education